Invitro Comparative Antifungal studies of Alphonsea sclerocarpa with Local herbal shampoo against clinically isolated Aspergillus (International Journal of Scientific Research and Management (IJSRM), 2015)
The present study aimed to evaluate the antifungal activity of Alphonsea sclerocarpa by comparing with local herbal shampoo (Prakruthi vanam shampoo) available in Madanapalle, Chittoor district,Andhra Pradesh. Clinical isolate of pathogenic fungi Aspergillus flavus was selected and plated on Potato Dextrose Agar. The plant samples were extracted with solvent methanol and the test Shampoo was diluted in water to get 1:5, 1:10 dilutions. The antifungal activity of both the plant extract and local herbal shampoo were tested against pathogenic fungus Aspergillus flavus by agar well – diffusion method. Both plant extract and shampoo shows antifungal activity, in which shampoo was effective against the tested fungi, whereas plant extract were showed moderate antifungal activity in comparison with shampoo.